Towards recovery in Pacific Asia - Segal, Gerald, 1953-; Goodman, David S. G. (ESRC Pacific Asia Programme (Series), 2000)
Attempts to define the Asian Crisis and its future course continue to be hotly contested. Towards Recovery in Pacific Asia deals with financial and industrial reform, defence policies, the 'Asian-Values' debate, corruption and croneyism; as well as China, Japan and intra-regional affairs. Rather than trying to resolve the heated debate about the causes of the crisis, this book reflects on underlying trends to examine the possible paths of recovery. Bringing together experts in the field, Towards Recovery in Pacific Asia suggests that recovery is by no means impossible nor as.